Essays on classical and Marxian political economy ;Collected essays IV - Hollander,Samuel (Routledge, 2013)
Samuel Hollander’s work has been provoking debate for over four decades. This book brings together key contributions of recent years, in addition to some brand new pieces. The essays are introduced by a Preface in which Hollander reflects on his past work and reactions to it.